2014
DOI: 10.1142/s0217751x14420093
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of radioactive trace impurities with μBq-sensitivity in Borexino

Abstract: Borexino has set new standards in the field of ultra-low background experiments. Such a success was only possible by a strict quality control program during the construction phase of the experiment. In this paper, we describe how construction materials and auxiliary systems of the Borexino detector were screened for their residual radioactivity with unprecedented high sensitivity. The highly sensitive assay techniques developed for this purpose were also used to validate the purity of water and nitrogen used i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…Hence, a further 222 Rn reduction by cleaning attempts was not measurable within our sensitivity. Again it was confirmed that stainless steel TIG-welds do not represent a notable additional source of 222 Rn, which is in tension with findings from other experiments [14,20].…”
Section: Stainless Steelsupporting
confidence: 64%
“…Hence, a further 222 Rn reduction by cleaning attempts was not measurable within our sensitivity. Again it was confirmed that stainless steel TIG-welds do not represent a notable additional source of 222 Rn, which is in tension with findings from other experiments [14,20].…”
Section: Stainless Steelsupporting
confidence: 64%
“…• the realization of the CTF; 17 • the purification of liquid scintillation, water and Nitrogen; 18,23,25 • selecting the materials concerning the ID and the OD, nylon, PMTs, and plant components and installations; 19,21,22 • the assembling of the nylon vessels and the installation of the detector and its subsystems; 20 • the procedures for the pseudocumene procurement and the detector filling; 24,27 • the detector calibration; 26 • the data analysis. 28 …”
mentioning
confidence: 99%
“…Testing HPN and RPN it turned out that they do not fulfill the above specifications therefore we worked on a suitable purification method and in parallel searched also on the marked for enough pure gas. Results obtained for nitrogen from different European suppliers and of different qualities are summarized in Table 3 [24]. In most cases the requirement for argon was met.…”
Section: Purification Of Nitrogenmentioning
confidence: 99%
“…Argon and krypton concentrations were always within the specifications [24]. HPN 2 was also used to produce synthetic air needed for the inflation of the inner vessel and the radon barrier balloons.…”
Section: Purification Of Nitrogenmentioning
confidence: 99%
See 1 more Smart Citation